Do RNA modifications contribute to modulation of immune responses in allergic diseases? - Kudrin, Pavel; Rebane, Ana (Frontiers in Allergy, 2023)
RNA modifications have emerged as a fundamental mechanism of post-transcriptional gene regulation, playing vital roles in cellular physiology and the development of various diseases. While the investigation of RNA modifications has seen significant advancements, the exploration of their implication in allergic diseases has been comparatively overlooked. Allergic reactions, including hay fever, asthma, eczema and food allergies, result from hypersensitive immune responses, affecting a considerable population worldwide. Despite the high prevalence, the molecular mechanisms underlying these responses remain partially understood. The potential role of RNA modifications in modulating the hypersensitive immune responses has yet to be fully elucidated. This mini-review seeks to shed light on potential connections between RNA modifications and allergy, highlighting recent findings and potential future research directions. By expanding our understanding of the complex interplay between RNA modifications and allergic responses, we hope to unlock new avenues for allergy diagnosis, prognosis, and therapeutic intervention.